Processing renewable and waste-based feedstocks with fluid catalytic cracking: Impact on catalytic performance and considerations for improved catalyst design - Mastry, Melissa Clough; Dorazio, Lucas; Fu, James C.; Gómez, Juan Pedro; Sedano, Sergio; Ail, Snehesh S.; Castaldi, Marco J.; Yilmaz, Bilge (Frontiers in Chemistry, 2023)
Due to both social and regulatory pressures, many industries are redefining their strategies and goals regarding sustainability and renewable sourcing. The refining industry, which provides most of the world’s transportation fuels (including gasoline, diesel, and jet fuel) and much of the world’s raw materials, is also making adjustments. Refiners around the globe are either considering or are actively replacing a portion of their crude oil inputs originating from fossil sources with alternative sources, including recycled materials (plastics, urban waste, mixed solid waste) and renewable materials (bio-mass waste, vegetable oils). In this report, we explore these concepts, specifically focusing on the fluid catalytic cracking (FCC) operation. Five pyrolysis oils, obtained from municipal solid waste and biogenic material (olive stones/pits), were fully characterized and tested against a standard fluid catalytic cracking (FCC) vacuum gasoil (VGO) feed in a bench scale reactor using an FCC catalyst at 10% loading to simulate FCC co-processing. Despite having unique feed properties, including high Conradson carbon (e.g., up to 19.41 wt%), water (e.g., up to 5.7 wt%), and contaminants (e.g., up to 227 ppm Cl) in some cases, the five pyrolysis oils gave similar yield patterns as the VGO. Gasoline was slightly (ca. 1 wt%) higher in all cases and LPG slightly (ca. 1 wt%) lower. Olefinicity in the LPG streams were unchanged, bottoms and light cycle oil (LCO) showed no significant changes, while dry gas was slightly (up to –0.2 wt%) lower. Coke selectivity was also relatively unchanged (maximum -7.7 wt%, relatively), suggesting minimal to no heat balance concerns when co-processing in an industrial FCC unit. The results demonstrate the applicability of municipal solid waste and biogenic originating pyrolysis oils into a refinery.